2017
DOI: 10.1371/journal.pone.0180894
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of zone-specific protein and metabolite profiles within nitrogen-fixing Medicago truncatula-Sinorhizobium medicae nodules

Abstract: Symbiotic nitrogen fixation (SNF) between rhizobia and legumes requires metabolic coordination within specialized root organs called nodules. Nodules formed in the symbiosis between S. medicae and barrel medic (M. truncatula) are indeterminate, cylindrical, and contain spatially distinct developmental zones. Bacteria in the infection zone II (ZII), interzone II-III (IZ), and nitrogen fixation zone III (ZIII) represent different stages in the metabolic progression from free-living bacteria into nitrogen fixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Interestingly, HslU-and HslV-eGFP also appeared to form punctate loci, although to a lesser extent than ClpXP1-eGFP. The lack of zone specificity for HslUV-eGFP and ClpXP1-eGFP was consistent with previous studies (8,9).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, HslU-and HslV-eGFP also appeared to form punctate loci, although to a lesser extent than ClpXP1-eGFP. The lack of zone specificity for HslUV-eGFP and ClpXP1-eGFP was consistent with previous studies (8,9).…”
Section: Discussionsupporting
confidence: 92%
“…HslUV and ClpXP protein distributions are not zone specific. Nodules formed in the symbiosis between M. sativa and S. meliloti are indeterminate and form developmental zones along the nodule longitudinal axis, each containing unique protein, metabolite, and transcript profiles (8,9). Therefore, if HslUV and ClpXP proteins accumulate in particular zones within the nodule, this may indicate that they play a specific role in SNF development or that their protein-protein interactions would be limited to gene products in that region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, nodule proteomics has been used to examine the proteome during field growth conditions (Delmotte et al 2010), to compare root nodules and stem nodules (Delmotte et al 2014), and to identify NifA-regulated proteins (Salazar et al 2010). Studies have compared the proteomes of nodules of different maturities or ages (Delmotte et al 2014;Nambu et al 2015;Marx et al 2016), and recently, proteomes of three zones from the same nodules were independently isolated and evaluated (Ogden et al 2017). These studies have revealed how the proteome changes during symbiotic development, and they complement and extend conclusions generated using transcriptomics.…”
Section: Proteome Studies Of Rhizobiamentioning
confidence: 99%
“…Others have compared the metabolite profile of effective and noneffective nodules to identify metabolic processes specifically active during SNF (Ye et al 2013;Gemperline et al 2015). As with transcriptomics and proteomics, metabolomics of nodules of different age or maturity has been performed to examine developmental progression (Lardi et al 2016), and zone-specific metabolite analyses have been performed (Ogden et al 2017). Metabolomics has further been employed to compare the metabolome of nodules from different plants containing the same rhizobial strain (Lardi et al 2016).…”
Section: Metabolite Analysesmentioning
confidence: 99%